Plasmonic tunable Ag-coated gold nanorod arrays as reusable SERS substrates for multiplexed antibiotics detection. Issue 4 (11th January 2021) - Peng, Xiaoya; Li, Dan; Li, Yuanting; Xing, Haibo; Deng, Wei
Abstract : The AgNPs/GNRs arrayed SERS chip is fabricated by self-assembly and electrodeposition method and reused for on-field detection of antibiotics in practical samples. Abstract : Antibiotic contaminants in aqueous media pose a serious threat to human and ecological environments. Therefore, it is necessary to develop robust strategies to detect antibiotic residues. For this purpose, a self-assembly and in situ electrochemical reduction method is utilized to tailor silver nanoparticles (AgNPs)-coated GNRs (AgNPs/GNRs) large-scale vertical arrays. These AgNPs/GNRs arrays exhibit outstanding surface-enhanced Raman scattering (SERS) activities because of abundant Raman hot-spots among the adjacent AgNPs and GNRs, but also excellent stability and reproducibility due to the close-packed arrayed nanostructure. These remarkable features validate this arrayed substrate for high-sensitivity 4-aminothiophenol analysis with a detection limit of 0.35 pM and self-cleaning via electrochemical stripping of the adsorbed analytes and AgNPs from the GNRs arrays, therefore realizing renewable SERS applications. Moreover, the distinct SERS performance of AgNPs/GNRs arrays is verified via the analysis of multiplexed antibiotics at tens of picomolar level and no apparent changes of SERS activities are observed when recyclability is explored. The result demonstrates that the proposed AgNPs/GNRs arrays provide a novel strategy for avoiding conventional, disposable SERS substrates, as well as expanding SERS applications for simultaneous sensing and stripping of environmental contaminants.